A formação do professor não especialista em conceitos elementares do bloco tratamento da informação: um estudo de caso no ambiente computacional - Santos, Sandra da Silva (2003)
The aim motivating this dissertation was to investigate the possibilities offered by the computational environment of the Tabletop software in the formation process for elementary knowledge of statistics, in order to respond to the following research question: "what characteristics describe the processes by which mathematical concepts of teachers related to handling data are formed and developed with the help of a computational environment?" To this end, a case study of a teacher of the initial series of Ensino Fundamental (students aged 6-11years) was developed. The teacher worked in a school in the public sector of the state of São Paulo. The field research lasted for eight months and contemplated two moments: the first concerned teacher education and occurred through both individual meetings between the teacher and the researcher and collective meetings (workshops); the second moment related to the teaching activities of the case-study teacher in her interactions with students and with other teachers. In addition, a series of diagnostic instruments, interviews and tests were administered at the beginning and end of the data-collection period, with each test involving both paper and pencil and computer activities. The results obtained in each of these moments were analysed according to three perspectives: the mathematical perspective, the technological perspective and the teacher's perspective. By the end of the investigation, the results suggested that the teacher had made substantial advances in relation to her mathematical knowledge, her mastery of the Tabletop environment and her confidence to develop data handling activities for her students and for other teachers These results suggest that the collection and organisation of data in the tables represent an important stage in the study of data-sets and that the computer, or more particularly Tabletop, can contribute in a significant way to the understanding of graphs and tables extracted during the manipulation of data. However, at the same time that Tabletop can act as a facilitory agent in the learning of statistical knowledge, an inadequate use of particular Tabletop resources can hinder the study of some aspects of data representation